Pengaruh Gaya Kepemimpinan Transformasional, Self-Efficacy dan Achievement Motivation Terhadap Kinerja Trader - , Niken Yuliatun Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The performance of a trader in the company named futures are at the forefront of the successful achievement of the performance of the company to survive amid the competitors of futures business. The purpose of this study to determine the factors that affects the performance of a trader in the futures firm. This study analysis the effect of transformational leadership style, self -efficacy, and achievement motivation on the performance of the traders. The object of this study is PT. Millenium Penata Futures region of Central Java and Yogyakarta. A model has been constructed and three research hypotheses have been formulated. Methods of data collection is by distributing questionnaires. This study uses 100 respondents and all respondents are traders of PT. MPF from region of Central Java and Yogyakarta. Analysis of data is using linear regression with the computer program called SPSS 19. The results showed that the three independent variable, which are: leadership style, self -efficacy and achievement motivation has a positive and significant impact on the performance of the trader.